Pembinaan Kepada Pengurus Di Ponpes Mukhtar Syafa'at Blokagung Tegalsari Banyuwangi Tentang Kepemimpinan Dalam Islam Menurut Al-Qur'an Dan Hadist - Mahmudah Mahmudah; Muhammad Imam Khaudli (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Leaders and leadership are daily problems in the life of society, organization, business, nation and state. The progress and setbacks of society, organization, business, nation and state are influenced by their leaders in social life, organization, business, nation and state. This service aims to explain the basis and foundation of Islamic leadership in the Qur'an and Hadith to the administrators of the Mukhtar Syafa'at Islamic Boarding School Blokagung Banyuwangi. The essence of this service is that a leader must serve the people he leads with love and sincerity as well as the pesantren administrators who devote themselves to the pesantren to carry out the task of advancing the pesantren and applying the knowledge that has been obtained to be applied to the younger students under level with full trust, fairness, and responsibility because every action will definitely be held accountable before Allah SWT.